Advances in Synthesis of Metallic, Oxidic and Composite Powders (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Advances in synthesis of metallic, oxidic and composite powders were presented via the following methods: ultrasound-assisted leaching¸ ultrasonic spray pyrolysis, hydrogenation, dehydrogenation, ball milling, molten salt electrolysis, galvanostatic electrolysis, hydrogen reduction, thermochemical decomposition, inductively coupled thermal plasma, precipitation and high pressure carbonation in an autoclave. This Special Issue contains 17 papers from Europe, Asia, Australia, South Africa and the Balkans. The synthesis was focused on metals: Co, Cu; Re; oxides: ZnO, MgO, SiO2; V2O5; sulfides: MoS2, core shell material: Cu-Al2O3, Pt/TiO2; compounds: Ca0.75Ce0.25ZrTi2O7, Mo5Si3, Ti6Al4V. The environmentally friendly strategies were presented at the carbonation of olivine, treatment of acid mine drainage water and production of vanadium oxide.